PERTUTURAN SITUASI DIGLOSIA PONDOK PESANTREN MODERN AL-SYAIKH ABDUL WAHID KOTA BAUBAU: KAJIAN SOSIOLINGUISTIK - Aisya Kahaz, Waode Sitti (Universitas Hasanuddin, 2019)
Language selection done by the speakers of the language so that it led to a situation of language that is diglosia to pay attention to the use of the languages of Indonesia, foreign language, and local languages in different situations. The aims of study were,(1) describe the situation in a conversation kediglosiaan Modern Boarding School of Al- Syaikh Abdul Wahid Baubau City and (2) reveal a situation in a conversation kediglosiaan Modern Boarding School Al- Syaikh Abdul Wahid Baubau City City in the realm of formal and informal. This research is a qualitative descriptive study. This research data in the form of units of speech students tsanawiyah in Modern Boarding Al-Syaikh Abdul Wahid. The method used is the method refer to techniques refer libat ably, check out free libat ably, engineering techniques and record noted. As for the method of data analysis was descriptive. Model of data analysis is the analysis of flows that consist of three strands of activities that occur simultaneously, i.e. the reduction of the data, the presentation of data, and the withdrawal of the summary. The results of this research show that the situation of the diglosia in Modern boarding schools students conversation Al-Shaykh ' Abd al Wahid Baubau Town there are 12 speech; 4 speech variety of formal (official), and 8 speech is colloquial variety (and familiar).